A Survey and Review of GSM Base Transceiver System Installation, Architecture and Uplink/Downlink - Adhikari, Manjish (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
With the advent of development in LTE system, eNodeB the revolutionised version of BTS is used for a connection between BSC and the users. A better and improved system increases the capacity and the functionality of the mobile wireless communication system. A Base Transceiver System (BTS) is a system in a mobile communication network that houses radio receivers and is used for wireless communication between users and network providers that is under the control of Base Switching Controller (BSC) and then the exchange. This paper deals with the study of a ground based GSM Base Transceiver System (BTS) and it’s installation process, architecture, internal structures, the process involved in the uplink and downlink call procedures and the future works. This study is based on the visit to a ground based BTS at BSNL regional training centre (RTTC), Hyderabad during the EETP course. The observations made are duly recorded, reviewed and presented for a better understanding of a mobile BTS system.